Non‐serotinous woody plants behave as aerial seed bank species when a late‐summer wildfire coincides with a mast year. Issue 19 (17th September 2014) - Pounden, Edith; Greene, David F.; Michaletz, Sean T.
<x xml:space="preserve">Abstract</x> Abstract Trees which lack obvious fire‐adaptive traits such as serotinous seed‐bearing structures or vegetative resprouting are assumed to be at a dramatic disadvantage in recolonization via sexual recruitment after fire, because seed dispersal is invariably quite constrained. We propose an alternative strategy in masting tree species with woody cones or cone‐like structures: that the large clusters of woody tissue in a mast year will sufficiently impede heat transfer that a small fraction of seeds can survive the flaming front passage; in a mast year, this small fraction would be a very large absolute number. In Kootenay National Park in British Columbia, we examined regeneration by Engelmann spruce (Picea engelmannii), a non‐serotinous conifer, after two fires, both of which coincided with mast years. Coupling models of seed survivorship within cones and seed maturation schedule to a spatially realistic recruitment model, we show that (1) the spatial pattern of seedlings on a 630 m transect from the forest edge into the burn was best explained if there was in situ seed dissemination by burnt trees; (2) in areas several hundred meters from any living trees, recruitment density was well correlated with local prefire cone density; and (3) spruce was responding exactly like its serotinous codominant, lodgepole pine (Pinus contorta). We conclude that non‐serotinous species can indeed behave like aerial seed bank species in mast years if the fire takes place late in the seed maturation period. Using the example of the circumpolar boreal forest, while the joint probability of a mast year and a late‐season fire will make this type of event rare (we estimate P = 0.1), nonetheless, it would permit a species lacking obvious fire‐adapted traits to occasionally establish a widespread and abundant cohort on a large part of the landscape.